2019
DOI: 10.1007/s10803-019-04056-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Atypical Development: A Role of Day-Care Workers?

Abstract: Identifying the early signs of developmental disability is important for ensuring timely diagnosis and early intervention. Day-care workers may be in a prime position to notice potential developmental deviations, but it is unclear if they can accurately recognize subtle early signs of atypical development. Sixty day-care workers examined home-videos of very young children with fragile X syndrome and typically developing children. Results indicated that most day-care workers can distinguish typical and atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…Other studies have presented similar results, for example, Nilsson Jobs et al (58) found that, compared to parents, preschool staff rated autism symptoms more in accordance with the health care staff. In line with a study by Zhang et al (51), we believe that the special education teachers' special knowledge and experience were crucial for detection of signs of autism and level of agreement between the two examiners. In the present study, the preschool special education teachers were able to recognize developmental impairment in respect of joint attention behaviours.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies have presented similar results, for example, Nilsson Jobs et al (58) found that, compared to parents, preschool staff rated autism symptoms more in accordance with the health care staff. In line with a study by Zhang et al (51), we believe that the special education teachers' special knowledge and experience were crucial for detection of signs of autism and level of agreement between the two examiners. In the present study, the preschool special education teachers were able to recognize developmental impairment in respect of joint attention behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have highlighted that preschool staff can effectively detect early symptoms of autism and other atypical features in early development (51)(52)(53)(54)(55), also in low-income and multiethnic settings (56,57). Day-care workers often have education in child development, as well as experience in working with children with diverse disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, as noted, it may be for reasons other than disabilities that children have SEN in preschool, and the Swedish Education Act consequently states the preschool's responsibility to identify and respond to children's need for special support for physical, mental, or other reasons (SFS 2010, 800). A recent study found that most preschool professionals can distinguish typical and atypical developments after observing children's behaviour, demonstrating they could play an important role to identify SEN (Zhang et al 2019), which is important for implementing early interventions effectively. In our study, the teachers' repeated and varied observations with TIS-S, seem to have prevented a static picture of children's social play behaviour, in favour of a more contextual assessment.…”
Section: Importance Of Outcomementioning
confidence: 99%
“…There are many features of early childcare settings that can facilitate the identification of children who show signs of delay or vulnerabilities. Registered Early Childhood Educators (RECEs) are trained in child development, see families on a regular basis, have multiple opportunities to observe a child, and can offer connections to other organizations and services when there is an identified need (36,37). Regular surveillance and screening already occur in school-aged children and it is accepted that using teacher-reported instruments in schools can be an effective method for identifying school-aged children who show signs of delay or developmental vulnerability (38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%